مقاصد القرآن من خلال سورة يونس - رزقاوي خولة; غ ا زل مباركة; د. مايدي عبد الرحمن (جامعة عمار ثليجي الاغواط, 2023)
في ىذه الد ا رسة المعنكنة بمقاصد الق ا رف لسكرة سكنس فالق ا رف الكري كلب ا﵀ تعالى أنزلو عمى قمب نبيو ليكف ىدل كرحمة العالميف، فمذلؾ يجب العانية بو كما أنزؿ لأجمو لاستنباط المقاصد الق آ رنية التي اشتممت عمييا سكر يكنس، كمعرفة قضياىا كالإب ا رز الإعجاز البياني في الق ا رف الكري مف كؿ مقصد، كقد خمصت إلى مجمكعة مف نتائج أىميا، إف عم مقاصد السكر يعني عمى استخ ا رج دقائؽ معانييا كتدبرىا كيكصؿ إلى معرفة الحؽ في تفسير كلب ا﵀ ، كاشتمالو عمى كثير مف القضايا، العقيدة كالأحكا كغيرى مف مقاصد الق ا رف. كيعد شيخ محمد الطاىر ابف عاشكر مف كبار أئمة التفسير المعاصريف، فجاء في تفسيره لسكرة يكنس: الإعجاز، التشريع ، ضرب الأمثاؿ، المكاعظ، القصص، كىذه المباحث كانت مكضكع د ا رستنا يتككف مف فصميف، عنكاف الفصؿ الأكؿ: مصطمحات كمفاىي كالفصؿ الثاني المقاصد الق آ رنية لسكرة يكنس ك يبدا بمقدمة كينتيى بخاتمة ، غايتنا مف ىذا البحث معرفة مقاصد الق ا رنية لسكرة يكنس عند طاىر ابف عاشكر كممات افتتاحية: مقاصد الق ا رن، سورة يونس التفسير ، طاىر ابن عاشور summary: In this study entitled “The Purposes of the Qur’an for Surat Sunis,” the Holy Qur’an is the word of God Almighty, revealed to the heart of His Prophet, to be the guidance and mercy of the worlds. And I concluded a set of results, the most important of which is that the knowledge of the purposes of the suras means extracting the subtleties of their meanings and contemplating them, and leads to knowing the truth in the interpretation of God’s words, and its inclusion of many issues, belief, rulings, and other purposes of the Qur’an. Sheikh Muhammad Al-Taher Ibn Ashour is considered one of the great contemporary imams of interpretation. In his interpretation of Surat Yunus, he mentioned: miracles, legislation, proverbs, sermons, stories, and these topics were the subject of our study consisting of two chapters. It begins with an introduction and ends with a conclusion. Our aim in this research is to know the Quranic purposes of Surat Yunus according to Taher Ibn Ashour. Introductory words of the purposes of the Qur’an, Surat Yunus, the interpretation, Taher Ibn Ashour